Evocative allusions in Matthew: Matthew 5:5 as a test case - Brawley, Robert L. (HTS teologiese studies, 2003)
Combining theories of intertextuality and abductive reasoning, this article demonstrates the figurative nature of scriptural allusions in Matthew. Allusions form figurations that open new perspectives for readers inasmuch as the source text and the new text stand in a tensive relationship in which each modifies the other and in which together they evoke meaning beyond the mere sum of the two independent texts. Allusions also form figurations inasmuch as arguments that are analogous to logic. Surprising, original, uncanny correlations between the source text and the new text involve what Charles Peirce called abductive reasoning which also challenges constructs of reality. This article interprets Matthew 5:5 as an allusion to the Abrahamic promise of the inheritance of the land and the blessing of all the families of the earth mediated through Psalm 36 (LXX) and describes the figurative nature of the allusion using Harold Bloom’s revisionary ratios. Another version of the article will also be published in Kim, P & Ringe, S (eds), Literary encounters with the reign of God: Essays in honor of Robert C Tannehill, Harrisburg, PA: Trinity Press International (Forthcoming).